The Great London Plague of 1665 and the US COVID-19 Pandemic Experience Compared - O'Hara, Frank (Maine Policy Review, 2021)
Using Daniel Dafoe's Journal of the Plague Year, Frank O'Hara examines the experience of the plague, the reactions of people, and changes to social cohesion and compares the current COVID-19 pandemic. These isses get at basic human reactions to crisis, and the similarities and differences between the 17th and 21st centuries are instructive.
Keywords: Daniel Dafoe; A Journal of the Plague Year